2022
DOI: 10.1186/s12882-021-02652-z
|View full text |Cite
|
Sign up to set email alerts
|

Association between bone mineral metabolism and vascular calcification in end-stage renal disease

Abstract: Background Development of vascular calcification is accelerated in patients with end-stage renal disease. In addition to traditional risk factors of cardiovascular disease (CVD) abnormal bone and mineral metabolism together with many other factors contribute to the excess cardiovascular burden in patients on dialysis. Aortic calcification score and coronary calcification score are predictive of CVD and mortality. The aim of this study was to evaluate the possible relationship between arterial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 50 publications
(56 reference statements)
1
7
0
Order By: Relevance
“…Moreover, 18 F-NaF uptake in the arterial wall correlates with risk factors for atherosclerosis [ 56 ]. A recent study demonstrated independent positive associations between 18 F-NaF uptake in bone, histomorphometric parameters of bone turnover in bone biopsies and arterial calcification in end-stage renal disease patients [ 57 ], in line with a previous study of bone biopsy-based histomorphometric parameters of bone turnover and coronary calcification in dialysis patients [ 58 ].…”
Section: Evaluation Of Fracture Risksupporting
confidence: 77%
“…Moreover, 18 F-NaF uptake in the arterial wall correlates with risk factors for atherosclerosis [ 56 ]. A recent study demonstrated independent positive associations between 18 F-NaF uptake in bone, histomorphometric parameters of bone turnover in bone biopsies and arterial calcification in end-stage renal disease patients [ 57 ], in line with a previous study of bone biopsy-based histomorphometric parameters of bone turnover and coronary calcification in dialysis patients [ 58 ].…”
Section: Evaluation Of Fracture Risksupporting
confidence: 77%
“…Forty-five articles were included in this review [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ] ( Figure 1 ), to which were added selected articles on methodological and other aspects. Findings in the articles are summarized in the following sections and in Tables S1–S6 in the Supplementary Material .…”
Section: Resultsmentioning
confidence: 99%
“…Several studies dealt with one arterial bed only, i.e., coronary arteries [ 16 , 17 , 18 , 20 , 29 , 30 , 31 , 38 , 39 , 44 ], global heart [ 22 , 23 , 24 , 25 , 27 , 34 ], pulmonary arteries [ 11 ], left carotid artery [ 28 ], aorta [ 26 , 32 , 41 , 42 , 48 , 49 ], abdominal aorta [ 13 , 33 , 45 ], or several arterial beds [ 5 , 6 , 7 , 8 , 9 , 10 , 12 , 14 , 15 , 21 , 35 , 36 , 37 , 40 , 41 , 43 , 46 , 47 ]. Eight reports were experimental animal studies [ 5 , 6 , 32 , 42 , 43 , 45 , 48 , 49 ], and one was an image case report [ 44 <...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies suggest an association between bone mineral metabolism and vascular calcifications in CKD patients and an impact of bone turnover on their development [ 34 ]. There is also evidence of the reduced progression of VCs after the improvement in bone status [ 35 ].…”
Section: Discussionmentioning
confidence: 99%